Identifying key safety investments needed for arctic shipping via a fuzzy analytic hierarchy process (FAHP) approach - Junjie Wan; Raphael Baumler; Dimitrios Dalaklis (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
The retreating ice coverage and reduced (ice) thickness scientifically recorded in the wider Arctic region, during the last few decades, are transforming it into a more accessible operating environment. Vessels engaged in maritime transport activities can now navigate the already established routes for more extended periods each year. With this background, Arctic shipping routes have attracted the interest of academics and maritime stakeholders because of the potential distance reduction compared to other existing (and often viewed as) conventional routes utilizing the Suez and Panama Canals today. However, the existing Arctic shipping environment requires specific future safety investments. This paper intends to provide input towards better-informed decision-making and identification of priority investments needed to improve the level of safety related to the Northern Sea Route (NSR) and Northwest Passage (NWP). A multi-attribute decision-making methodology, the Fuzzy Analytic Hierarchy Process, is applied to rank the various proposed safety investments. The results indicate that “infrastructure and facility” should come first, followed by “personnel,” “technology,” “measure,” and “management” investments. Ice monitoring and weather forecasting, strengthening Arctic seafaring expertise, and icebreakers stand out as the top three most important future investments required in the region.